2020
DOI: 10.1177/0146167220923853
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Social Rank: Income Increases Buy More Life Satisfaction in More Equal Countries

Abstract: How do income and income inequality combine to influence subjective well-being? We examined the relation between income and life satisfaction in different societies, and found large effects of income inequality within a society on the relationship between individuals’ incomes and their life satisfaction. The income–satisfaction gradient is steeper in countries with more equal income distributions, such that the positive effect of a 10% increase in income on life satisfaction is more than twice as large in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 94 publications
(119 reference statements)
1
15
0
1
Order By: Relevance
“…More recent research, however, has suggested instead that the relative ranked position of an income within a comparison set determines judgments of both wage satisfaction (Brown et al, 2008) and life satisfaction more generally (Boyce et al, 2010). The latter finding has been replicated in many countries (Macchia et al, 2020) and is consistent with effects of income inequality on income/well-being gradients (Quispe-Torreblanca et al, 2021). Similarly to PF&M, Brown et al (2008) gave students hypothetical wages but presented them in the context of different contextual wage distributions.…”
Section: Ensemble Representations and Ensemble Judgmentsupporting
confidence: 68%
“…More recent research, however, has suggested instead that the relative ranked position of an income within a comparison set determines judgments of both wage satisfaction (Brown et al, 2008) and life satisfaction more generally (Boyce et al, 2010). The latter finding has been replicated in many countries (Macchia et al, 2020) and is consistent with effects of income inequality on income/well-being gradients (Quispe-Torreblanca et al, 2021). Similarly to PF&M, Brown et al (2008) gave students hypothetical wages but presented them in the context of different contextual wage distributions.…”
Section: Ensemble Representations and Ensemble Judgmentsupporting
confidence: 68%
“…This mechanism could account for some findings that people who live in more objectively unequal social contexts report reduced wellbeing (e.g., Layte, 2012; Oishi et al, 2011; Vilhjalmsdottir et al, 2016; Zhang & Churchill, 2020). At the same time, however, a recent meta‐analysis found that the impact of inequality on wellbeing did not differ from zero (Ngamaba et al, 2018; see e.g., Delhey & Dragolov, 2014; Zhao, 2012), leading researchers to suggest that there may be important moderators of this relationship, including GDP (Ngamaba et al, 2018), individual income (Quispe‐Torreblanca et al, 2021; see also Cheung & Lucas, 2016), perceived social mobility (e.g., Sagioglou et al, 2019) and the concentration of inequality in the top or bottom of the distribution (Blesch et al, 2022; Tan et al, 2020).…”
Section: Consequences Of Economic Inequalitymentioning
confidence: 99%
“…In addition, the relationship between inequality and happiness can be mediated by social environment, with U.S. states with tighter controls (i.e., a greater number of strongly enforced rules and little tolerance for deviance) showing greater inequality and lower happiness relative to states with looser controls (Harrington and Gelfand 2014). Similarly, the income effect on satisfaction can be conditional on a country’s level of economic inequality, with a greater effect in a more equal society (Quispe-Terreblanca et al 2020).…”
Section: Background and Theorymentioning
confidence: 99%